A Bayesian analysis of associations between neighborhoods, spanking and child externalizing behavior. (May 2020) - Grogan-Kaylor, Andrew; Castillo, Berenice; Ma, Julie; Ward, Kaitlin P.; Lee, Shawna J.; Pace, Garrett T.; Park, Jisu
Highlights: Corporal punishment and neighborhood disadvantage are associated with increases in child behavior problems. Corporal punishment is equally deleterious across neighborhood contexts. Families may benefit from interventions that provide parents with non-physical discipline strategies. Bayesian estimation can incorporate information from previous empirical studies. Bayesian estimation allows researchers to accept the Null Hypothesis. Abstract: Background: A large body of research has found that corporal punishment is associated with increases in children's behavior problems. However, questions remain as to whether or not the relationship between corporal punishment and behavior problems is equally true across contexts. Objective: To examine the degree to which the effects of corporal punishment are equivalent across neighborhoods. Specifically, is corporal punishment equivalently associated with child behavior problems in neighborhoods that are perceived to be unsafe or disadvantaged, as compared to neighborhoods that are perceived to be less disadvantaged? Participants: 2703 participants in the Fragile Families and Child Wellbeing Study. Methods: We employed Bayesian regression methods, to examine the association of neighborhood disadvantage, corporal punishment, and their interaction, with child behavior problems. Results: Findings suggest that both neighborhood disadvantage (β = 0.070) and parental use of corporal punishment (β = 0.169) had main effect associations with child behavior. However, there was no evidence for an interaction of neighborhood disadvantage and corporal punishment use. Conclusions: Both corporal punishment and neighborhood disadvantage were associated with increases in child behavior problems. Corporal punishment appears to be equally deleterious across neighborhood contexts.